Correction: Reduced graphene oxide nanosheets decorated with Au–Pd bimetallic alloy nanoparticles towards efficient photocatalytic degradation of phenolic compounds in water. Issue 45 (7th November 2016) - Darabdhara, Gitashree; Boruah, Purna K.; Borthakur, Priyakshree; Hussain, Najrul; Das, Manash R.; Ahamad, Tansir; Alshehri, Saad M.; Malgras, Victor; Wu, Kevin C.-W.; Yamauchi, Yusuke
Abstract : Correction for 'Reduced graphene oxide nanosheets decorated with Au–Pd bimetallic alloy nanoparticles towards efficient photocatalytic degradation of phenolic compounds in water' by Gitashree Darabdhara, et al., Nanoscale, 2016, 8, 8276–8287.